LibraryNOTC - Mior Yusoff, Fatin Nurliyana; Abd Razak, Nur Fitrah; Razali, Nurul Syafiqah Azmini; Daud, Mohd Shamsul (Universiti Teknologi MARA, Kedah, 2017)
LibraryNOTC is a newly environmental approach for the libraries to practice in a way getting more acceptable among their users. This approach brings more outstanding existing of the libraries to fulfil their users’ needs beyond usual practice where there will be no tables and chairs provided. Nowadays people prefer attending places which can provide them a relaxing and casual environment while doing their leisure and relaxing activities such as reading and etc. with family members and friends. This scenario can be clearly seen in the recreational playground, in the hypermarket and other places such as mosque with mini garden inside or resting area. The ideas of LibraryNOTC, making the space expand and it creates a space without barriers. By having this LibraryNOTC concept, the physical space of the library will be widely decorated and designed with natural ecosystem concept that will give more panoramic and refreshing scene. The space in library may look wider as there are no chairs and tables around. Based on its common physical structure, the nature of having many tables and chair in the library actually contributes to uneasy and stressful environment which will affect the feeling of people who stay in the library. LibraryNOTC is believed would provide something new and fresh moods among the users. LibraryNOTC also will be able to lower down the library budget in buying and covering maintenance cost of the tables and chairs every year. The design and implementation of the new concept of LibraryNOTC allows they library to transform their traditional space with its tables and chairs, cubicles and stacks into a new concept that fostered learning and communication. The library can construct a flexible space with no chairs and tables. Thus, it solved the space problem as the number of library user increase every year. Besides, from maintenance point of view, without tables and chairs, the library can save their budget for replacing the damage items. Open spaces, it creates a space without barriers, here people would get together from different backgrounds, different fields of expertise, and share.